2019
DOI: 10.1182/blood-2019-126422
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Diffusion Weighted MRI (WB DWI) for the Management of Multiple Myeloma: High Concordance between MRI Diffuse Pattern and BONE Marrow Plasma CELL Infiltration RATE

Abstract: Background: Diffusion-weighted whole body MRI (WB-DWI) is a new functional imaging technique comprising anatomical and functional sequences with an emerging role in the management of multiple myeloma (MM) patients (pts) since it allows highly sensitive detection of diffuse bone marrow (BM) infiltration pattern and focal lesions, avoiding intravenous injections and radiation exposure. The aims of our study were 1) to test the correlation between plasma cells infiltration (BMPC) rate at BM biopsy and the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The BMPC percentage is critical for MM diagnosis, assessment of treatment efficacy, and monitoring for recurrence 1 . The BMPC percentage was significantly correlated with tumor burden and prognosis in MM 26–28 . Beta‐2‐microglobulin, a low‐molecular weight protein expressed on the surface of almost all normal nucleated cells and many tumor cells, is a major serum biomarker of tumor burden in MM and a component of R‐ISS staging system 4,7,29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMPC percentage is critical for MM diagnosis, assessment of treatment efficacy, and monitoring for recurrence 1 . The BMPC percentage was significantly correlated with tumor burden and prognosis in MM 26–28 . Beta‐2‐microglobulin, a low‐molecular weight protein expressed on the surface of almost all normal nucleated cells and many tumor cells, is a major serum biomarker of tumor burden in MM and a component of R‐ISS staging system 4,7,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…1 The BMPC percentage was significantly correlated with tumor burden and prognosis in MM. [26][27][28] Beta-2microglobulin, a low-molecular weight protein expressed on the surface of almost all normal nucleated cells and many tumor cells, is a major serum biomarker of tumor burden in MM and a component of R-ISS staging system. 4,7,29,30 In addition, the serum β 2 -microglobulin level was proved to be an independent predictor of survival in MM.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key features of DW-MRI is its high sensitivity in detecting diffuse bone marrow infiltration and focal lesions, which are characteristic of MM. Studies have shown that DW-MRI can detect more focal lesions compared to conventional radiography and has a high concordance with the bone marrow plasma cell infiltration rate [36], [38]. Additionally, changes in ADC values post-treatment have been correlated with response to chemotherapy, with responders showing a significant increase in ADC values, indicating a reduction in cellularity and a positive treatment effect [39], [44].…”
Section: Dw-mrimentioning
confidence: 99%
“…The main advantage of DW-MRI is its ability to provide both anatomical and functional information about bone lesions without the need for ionizing radiation or intravenous contrast agents. This makes it particularly useful for patients who are unable to undergo contrast-enhanced studies or who require repeated imaging for monitoring disease progression or response to therapy [38]- [43].…”
Section: Dw-mrimentioning
confidence: 99%
“…Other advances are also being implemented in the setting of imaging techniques. Whole-body diffusion-weighted MRI (WB-DWI) maintains the advantages of MRI to identify small lesions in bone marrow at diagnosis, but it also allows the quantification of residual disease through the apparent diffusion coefficient without the need for intravenous contrast and shows a good correlation with bone marrow infiltration, thus being superior to conventional MRI (91,92). Some preliminary studies have confirmed a benefit in PFS linked to the achievement of WB-DWI negativity after ASCT (93,94), additionally being a technique without ionizing radiation, which may overcome some of the limitations of PET-CT (95).…”
Section: Towards a Comprehensive Evaluation Of Tumor Burden: The Futurementioning
confidence: 99%